IMPLEMENTASI MEDIA KARTU TEMPEL DALAM PEMBELAJARAN MAJAS PUISI DI KELAS VIII SMPN 2 SELONG - Bq. Risnia Wati; Hary Murcahyanto; Rohayati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The purpose of this study was to explain how sticky cards were used in teaching poetic figures of speech in grade VIII.1 of SMPN 2 Selong; to reveal the experiences and difficulties encountered by teachers and students; and to examine how this medium contributes to deep learning. With one Indonesian language teacher and 27 students, this study employed a descriptive qualitative approach. Data were collected through documentation, observation, interviews or reflections, and a Google Form questionnaire. The Miles and Huberman model was then used to analyze the data through adjustment, presentation, and drawing conclusions. The results showed that sticky cards can increase student engagement, enthusiasm, collaboration, and understanding of figurative language. Because visual, audiovisual, and interactive learning media are considered more engaging and help them understand the material, research shows that students prefer them. Furthermore, sticky cards encourage students to discuss, relate ideas to real-life examples, and reflect on mistakes. This supports the principles of reflective learning, significant learning, and enjoyable learning. Therefore, sticky cards can serve as an effective alternative non-digital media to support Indonesian language learning.